2018
DOI: 10.3727/096504017x15061902533715
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of MicroRNA-147 Inhibits Cell Proliferation and Increases the Chemosensitivity of Gastric Cancer Cells to 5-Fluorouracil by Directly Targeting PTEN

Abstract: Gastric cancer is the fourth most common malignancy and the third leading cause of cancer-related deaths worldwide. This study aimed to investigate the expression patterns, biological roles, and underlying mechanisms of microRNA-147 (miR-147) in gastric cancer. The present study demonstrated that miR-147 was significantly upregulated in gastric cancer tissues and cell lines. Downregulation of miR-147 decreased cell proliferation and enhanced the chemosensitivity of gastric cancer cells to 5-fluorouracil (5-FU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 49 publications
2
32
1
Order By: Relevance
“…28,29 Shen et al found that knockdown of miR-147 enhanced the sensitivity of gastric cancer cells to 5-Fu by targeting PTEN and regulating the AKT signaling. 30 Meanwhile, miR-21 could enhance drug resistance to 5-Fu in PANC-1 cells by downregulation of PTEN. 31 In this study, we found that the downregulation of miR-486-5p markedly enhanced the anti-tumor effects of 5-Fu in PANC-1 cells via upregulating the expression of PTEN and suppressing the activation of AKT/ERK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Shen et al found that knockdown of miR-147 enhanced the sensitivity of gastric cancer cells to 5-Fu by targeting PTEN and regulating the AKT signaling. 30 Meanwhile, miR-21 could enhance drug resistance to 5-Fu in PANC-1 cells by downregulation of PTEN. 31 In this study, we found that the downregulation of miR-486-5p markedly enhanced the anti-tumor effects of 5-Fu in PANC-1 cells via upregulating the expression of PTEN and suppressing the activation of AKT/ERK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…17 Furthermore, miRNA-147 can inhibit cell proliferation and increase the chemosensitivity of GC to 5-FU by targeting PTEN. 18 It seems that the status of PTEN and FAK expression may be helpful for evaluating the response to target therapy and chemotherapy. Our study demonstrated distinguishable patient prognoses according to the PTEN/FAK expression, which may provide useful information and have clinical impact on GC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that EB virus miRNA miR-BART20-5p significantly increased 5-FU resistance of AGS1 gastric cancer cells by inhibiting BAD expression [56]. Similarly, miR-193-3p and miR-147 could promote 5-FU resistance of gastric cancer cells via directly suppressing their target gene PTEN [127,128]. Oncogenic miR-17 has been found to reduce 5-FU sensitivity of gastric cancer cells through silencing expression of DEDD [129].…”
Section: Mirnas and Resistance To Platinum Drugsmentioning
confidence: 99%